Structure of the hyperosmolality-gated calcium-permeable channel OSCA1.2 - Xin Liu (Nature Portfolio, 2018)
In plants, hyperosmolality stimuli triggers opening of the osmosensitive channels, leading to a rapid downstream signaling cascade. Here, the authors solve the cryo-EM structure of an osmosensitive channel from Arabidopsis OSCA1.2 in its inactivated state.